2007
DOI: 10.1007/s00402-007-0427-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal osteonecrosis and bone drilling parameters revisited

Abstract: Introduction During the drilling of the bone, the temperature could increase above 47 o C and cause irreversible osteonecrosis. The result is weakened contact of implants with bone and possible loss of rigid fixation. The aim of this study was to find an optimal conditions where the increase in bone temperature during bone drilling process would be minimal. Materials and methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
330
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(361 citation statements)
references
References 31 publications
11
330
2
2
Order By: Relevance
“…29,30 Research in rat, 31 canine, 32 and human bone 33,34 has shown that thermal damage delays bone healing, increases bone resorption, and can cause implant loosening or failure. Consequently, a variety of improved drill bits and finely tuned drilling parameters have been developed to reduce thermal necrosis, 29,[35][36][37] although irrigation, both cooled and room temperature, remains the simplest approach. 29,36 The contour and shape of drill burs influences the extent of thermal damage where some commercial drill bits produce less heat than standard equivalents.…”
Section: Microfracture Vs Drilling For Cartilage Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Research in rat, 31 canine, 32 and human bone 33,34 has shown that thermal damage delays bone healing, increases bone resorption, and can cause implant loosening or failure. Consequently, a variety of improved drill bits and finely tuned drilling parameters have been developed to reduce thermal necrosis, 29,[35][36][37] although irrigation, both cooled and room temperature, remains the simplest approach. 29,36 The contour and shape of drill burs influences the extent of thermal damage where some commercial drill bits produce less heat than standard equivalents.…”
Section: Microfracture Vs Drilling For Cartilage Repairmentioning
confidence: 99%
“…Consequently, a variety of improved drill bits and finely tuned drilling parameters have been developed to reduce thermal necrosis, 29,[35][36][37] although irrigation, both cooled and room temperature, remains the simplest approach. 29,36 The contour and shape of drill burs influences the extent of thermal damage where some commercial drill bits produce less heat than standard equivalents. 35 Kirschner-wires (or K-wires) are also commonly used, but have a smooth surface without threads and therefore do not remove bone debris, but compress it, leading to increased bone density (as in the MF of our study) and increased heat due to friction.…”
Section: Microfracture Vs Drilling For Cartilage Repairmentioning
confidence: 99%
“…Lee et al 3 performed drilling experiments on bovine bone in the ranges of 800 rpme3800 rpm and concluded that the bone drilling temperature rises with increase in drill speed. The effect of increase in feed rate on temperature is reported by Augustin et al 13 and Lee et al, 3 they found that the temperature decreases with increase in feed rate as the increase in feed rate increases the rate of heat generation rate but causes reduction in drilling time therefore less total heat is generated. The review of the effect of spindle speed on bone drilling temperature suggests no consistent trend.…”
Section: Introductionmentioning
confidence: 88%
“…During bone drilling the value of each response not their mean values must be as low as possible for minimum bone tissue injury. 13 Each combination of experiment is repeated three times and the average of the highest value of each response is considered for analysis.…”
Section: Experimental Designmentioning
confidence: 99%
“…have been reported [23][4] [5], but varying experimental conditions make comparisons among studies difficult. Whilst it is generally believed that a low rotational speed (around 1000 RPM) and a high feed rate (up to 1 mm/s) leads to a lower overall temperature elevation [23] [3]. The reason for the beneficial lower rotation speed is the reduction of friction.…”
Section: Introductionmentioning
confidence: 99%